(untitled) (Medico Legal Update, 2020)
Background: Lung cancer is one of the most common and serious types of cancer. Cigarette smoking is the main cause of lung cancer.The aims of this study was therefore to assess the risk factors of lung cancer patients in Babylon governorate including tobacco smoking , family history, and occupational exposures, measurement of radon gas in the bed room of patients with lung cancer. Patients and Methods: A case – control study was conducted in Babylon oncology center , Murjan medical city during the period from 8th of may to 2nd of september 2019. This center received all lung cancer patients in Babylon governorate. Results: The study showed that 43.3% of cases were in the age groups 60- 69 years. Males constitute 69.5 % of cases, seventy one percentage of cases were residing in a rural area. Smoking is the main risk factors of lung cancer in 75.8% , the risk of lung cancer in current smoker is three times more than that of non smoker .Those who had a family history of lung cancer constitute 8.3% ,of them 3.9% were first degree and 4.4% were second degree ,there was a significant association between lung cancer patients and first degree family history with lung cancer .Those who had a family history of other cancer was 23.6 % .The risk factors include radon exposure, asbestose, beryllium ,cadmium and diesel exposure were significant associated with lung cancer . The radon value in (77) patients of lung cancer were within exceptable limit.Conclusion : This study revealed that males, age group 60 and above, rural area and smoking is the main risk factors of lung cancer in Babylon city.There is highly significant association between smoking habits and lung cancer cases p-value<0.05.